The Great British baking show. Comfort bakes - Hollywood, Paul; Hollywood, Paul; Leith, Prue; Leith, Prue (Sphere an imprint of Little, Brown Book Group, 2024)
"Is there anything more comforting than the smell of a fresh bakewafting through the house? Paul, Prue and the 2024 bakers explore comfort in all its forms in these delectable, warm, cozy recipes. These include cakes for cheery family get togethers; recipes with a sense of nostalgia; hearty and warming bakes for cozy nights; and low-effort and quick concoctions that are an immediate balm. You'll find rhubarb upside-down cake, served with lashings of custard; butterscotch shortbread--the perfect dunking biscuit; cheesy, salty crumpets that couldn't be easier to make; a moreish malted chocolate and honeycomb layer cake, and so much more"--